Identification of Promising RILs for High Grain Zinc Through Genotype × Environment Analysis and Stable Grain Zinc QTL Using SSRs and SNPs in Rice (Oryza sativa L.) - Suman, K.; Neeraja, C. N.; Madhubabu, P.; Rathod, Santosha; Bej, Sonali; Jadhav, K. P.; Kumar, J. Aravind; Chaitanya, U.; Pawar, Smita C.; Rani, Surekha H.; Subbarao, Lella V.; Voleti, Sitapati R. (Frontiers in Plant Science, 2021)
Polished rice is one of the commonly consumed staple foods across the world, however it contains limited nutrients especially iron (Fe) and zinc (Zn). To identify promising recombinant inbred lines (RILs) for grain Zn and single plant yield, 190 RILs developed from PR116 and Ranbir Basmati were evaluated in Kh16 (Kharif: wet season) (Environment1-E1) and Rb17 (Rabi: dry season) (Environment2-E2) for ten traits viz., days to 50% flowering, plant height, panicle length , number of tillers, single plant yield (SPY), test weight, Fe and Zn in brown (IBR, ZBR) and polished rice (IPR, ZPR). A sub set of 44 contrasting RILs for grain Zn was also screened during Kh17 (Environment1-E3) and Rb18 (Environment2-E4). Stepwise regression analysis of 190 and subset of 44 RILs revealed the interdependence of ZPR, ZBR, IPR and IBR and negative association of grain Zn with single plant yield. Based on the Additive Main Effect and Multiplicative Interaction (AMMI) and Genotype and Genotype × Environment Interaction (GGE) analyses of the sub set of 44 RILs across four environments (E1-E4), six promising RILs were identified for ZPR with > 28 ppm. For SPY, five promising RILs across environment were noted. RIL G17 found to be promising for ZPR and SPY (Mean of 28.3 ppm for ZPR and 23.5 g for SPY). Mapping of 190 RILs with 102 simple sequence repeats (SSRs) resulted in 13 QTL for best linear unbiased estimates (BLUEs) of traits including advantage over check (AOC). Using genotype based sequencing (GBS), subset of 44 RILs was mapped with 1035 single nucleotide polymorphisms (SNPs) and 21 QTL were identified. More than 100 epistatic interactions between the QTL were observed. A major QTL viz., qZPR1.1 (PV 30.61%) and another QTL qZPR11.1 (PV 15.47%) were identified for grain Zn in polished rice. Two potential candidate genes related to transporters were identified based on network analyses in the genomic regions of QTL <3 Mb. The RILs identified for grain Zn and SPY were nominated for national evaluation as under rice biofortification and two QTL based on BLUEs can be used in the rice biofortification breeding programmes.